Some Properties of Two Autolytic-Defective Mutants of Streptococcus faecalis ATCC 9790 - Pooley, H. M. (1972)
The isolation and some properties of two mutants of Streptococcus faecalis ATCC 9790 (S. faecium) which autolyze at a much slower rate than the wild type are described. Compared with the wild type, mutant E71 autolyzed more slowly, contained less active but more latent autolysin in the isolated wall fraction, and possessed a wall of very similar chemical composition and degree of cross-bridging. Ultrastructural studies of exponential phase cells showed that cells of E71 were on the average slightly longer and had slightly thickened walls compared to the wild type. Mutant E81 autolyzed much more slowly, grew exponentially in long chains (8 to 40 cells compared with mainly diplococci), contained much less active and latent autolysin in the wall, and possessed a wall of very similar chemical composition but with about twice the content of N-terminal groups. Mutant E81 walls were more susceptible to isolated autolysin but possessed an autolysin of the same specificity as the wild type. Ultrastructurally E81 cells were, on the average, significantly longer and had thicker walls than the wild type. Mutant E71 may be partially blocked at either transport of autolysin to the wall or in conversion of latent to active autolysin. The pleitropic effects noted in mutant E81 have been taken to suggest a possible membrane defect and to support the role of the autolysin in cell separation.